The FGFR4 Homolog KIN-9 Regulates Lifespan and Stress Responses in Caenorhabditis elegans - Mallick, Avijit; Xu, Leo; Mehta, Sakshi; Taylor, Shane K. B.; Hosein, Hannah; Gupta, Bhagwati P. (Frontiers in Aging, 2022)
Fibroblast growth factor receptors (FGFRs) regulate diverse biological processes in eukaryotes. The nematode Caenorhabditis elegans is a good animal model for studying the roles of FGFR signaling and its mechanism of regulation. In this study, we report that KIN-9 is an FGFR homolog in C. elegans that plays essential roles in aging and stress response maintenance. kin-9 was discovered as a target of miR-246, a microRNA that is positively regulated by the Axin family member pry-1. We found that animals lacking kin-9 function were long-lived and resistant to chemically induced stress. Furthermore, they showed a reduced expression of endoplasmic reticulum-mediated unfolded protein response (ER-UPR) pathway genes, suggesting that kin-9 is required to maintain a normal ER-UPR. The analysis of GFP reporter-based expression in transgenic animals revealed that KIN-9 is localized in the intestine. Overall, our findings demonstrate that kin-9 is regulated by miR-246 and may function downstream of pry-1. This study prompts future investigations to understand the mechanism of miRNA-mediated FGFR function in maintaining aging and stress response processes.